Fiscal federalism, decentralization and economic growth: survey and meta-analysis - Baskaran, Thushyanthan; Feld, Lars P.; Schnellenbach, Jan (CESifo working papers, 2014)
The theoretical literature on the economics of fiscal federalism has identified several potential effects of government decentralization on economic growth. Much of the traditional literature focuses on the efficiency aspects of a decentralized provision of public services. However, decentralization may also increase growth by raising the ability of the political system to innovate and carry out reforms. On the contrary, some authors argue that decentralization increases corruption and government inefficiency. After a discussion of the theoretical arguments, we provide both a traditional survey and a meta-analysis of the empirical literature on decentralization and economic growth. Based on our survey, we identify open questions and discuss possible ways of answering them.
Keywords: Arbeitspapier; Graue Literatur